(untitled) (Scientific journal of the Fergana State University, 2023)
The peculiarities of the language of the work of art and the skill of creating a figurative image in Alisher Navoi’s epic “Lisonut-tayr” are described in the article. Phrases, proverbs, myths and legends related to folklore are analyzed. In the work of art, imagery and expressiveness reflect the environment of the time, the literary language, and the customs. The period of the poet’s life and social environment are reflected in the epic “Lisonut-tayr” though birds. In the works of Alisher Navoi various forms of artistic image and means of expression are analyzed.